2019
DOI: 10.1021/jacs.9b04712
|View full text |Cite
|
Sign up to set email alerts
|

Supertetrahedral Layers Based on GaAs or InAs

Abstract: The solid-state compounds M 15 Tr 22As32 and M 3Ga6As8 (M = Sr, Eu; Tr = Ga, In) were synthesized by heating the elements, and their crystal structures were determined by single-crystal and powder X-ray diffraction (space group C2/c). The structures are hierarchical variants of the HgI2 type and consist of layers of polymeric T5 (M 15 Tr 22As32) or T6 supertetrahedra (M 3Ga6As8), separated by strontium or europium cations. These compounds constitute hitherto unknown GaAs- or InAs-based supertetrahedral structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…This is dissimilar to other reports of p-type ternary compounds containing III−V fragments, such as in the supertetrahedral layered compounds Ae 15 Tr 22 As 32 and Ae 3 Ga 6 As 8 (Ae = Sr, Eu; Tr = Ga, In), in which there is a substantial decrease in mobility down to 0.2− 98 cm 2 •V −1 •s −1 going from the binary to ternary compounds. 89 High hole mobility within bulk samples at room temperature is uncommon but can still be found in some compounds, such as doped CsBi 4 Te 6 (700−1000 cm 90−92 The ordered nature of the In−Sb framework may be a key to the high mobility of Cs 8 In 27 Sb 19 . It was shown that defects may significantly affect the electronic and optical properties of III− V semiconductors.…”
Section: ■ Introductionmentioning
confidence: 99%
“…This is dissimilar to other reports of p-type ternary compounds containing III−V fragments, such as in the supertetrahedral layered compounds Ae 15 Tr 22 As 32 and Ae 3 Ga 6 As 8 (Ae = Sr, Eu; Tr = Ga, In), in which there is a substantial decrease in mobility down to 0.2− 98 cm 2 •V −1 •s −1 going from the binary to ternary compounds. 89 High hole mobility within bulk samples at room temperature is uncommon but can still be found in some compounds, such as doped CsBi 4 Te 6 (700−1000 cm 90−92 The ordered nature of the In−Sb framework may be a key to the high mobility of Cs 8 In 27 Sb 19 . It was shown that defects may significantly affect the electronic and optical properties of III− V semiconductors.…”
Section: ■ Introductionmentioning
confidence: 99%
“…[10] and Na 23 Si 9n+19 P 12n+33 with n = 0-3. [11] To the best of our knowledge this uncommon condensation mode was sparely observed only in KSi 2 P 3 , [7] B 2 S 3 , [12] Li 9 B 19 S 33 , [13] M 15 Tr 22 As 32 and M 3 Ga 6 As 8 (M = Sr, Eu; Tr = Ga, In) [14] and a few other mixedmetal T3 chalcogenides. [15] The possibility of the formation of homonuclear phosphorus bonding distinguishes the family of phosphidosilicates from the oxido-and nitridosilicates.…”
Section: Introductionmentioning
confidence: 99%
“…[7] In contrast, the introduction of small and weak electronegative metals yields threedimensional structures of vertex-shared tetrahedra [8] or supertetrahedra with sizes ranged from T2 to T5 [9] and the feature of supertetrahedral fusion in Li 2 SiP 2 , LiSi 2 P 3[10] and Na 23 Si 9n+19 P 12n+33 with n = 0-3. [11] To the best of our knowledge this uncommon condensation mode was sparely observed only in KSi 2 P 3 , [7] B 2 S 3 , [12] Li 9 B 19 S 33 , [13] M 15 Tr 22 As 32 and M 3 Ga 6 As 8 (M = Sr, Eu; Tr = Ga, In) [14] and a few other mixedmetal T3 chalcogenides. [15] The possibility of the formation of homonuclear phosphorus bonding distinguishes the family of phosphidosilicates from the oxido-and nitridosilicates.…”
mentioning
confidence: 99%
“…The basic building units of these compounds are SiP 4 tetrahedra condensed by vertices to T2 supertetrahedra (Figure 2, yellow) according to the Yaghi [ 20 ] notation. By zigzag fusion of these entities, which was sparely observed in related compounds, [ 6,10–11,21–28 ] chains are formed, depicted in turquoise in Figure 2. Further vertex‐edge condensation of these fused T2‐chain motifs – to the best of our knowledge only once observed [ 29 ] – yields in T2 layers, which are propagating in the ab plane, visualized by condensation of the blue T2 chains in Figure 2.…”
Section: Resultsmentioning
confidence: 71%